Advanced Security System Using Finger Vein Recognition (International Journal of Engineering and Computer Science, 2017)
The crime rate and robbery especially in bank is keep on increasing these days. Protecting personal and private information is now great challenge. The intelligent security system, biometrics, is now playing an irreplaceable role. Though there are lot of biometric systems available previously, each have their own disadvantages. In this paper we propose Finger vein recognition system which matches vascular pattern in an individual’s finger to previously obtained data. The proposed system uses only 0.8 seconds to verify one input finger vein sample and equal error rate is about 0.07% on a database of 100 subjects, demonstrating that the design approach can be effective than other biometric system.